(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to consideration of some aspects of hooliganism investigation. The method of commission is analyzed as an element of the forensic characteristics of the specified offense. It is noted that the method of committing a criminal offense is considered by most scientists to be the central element of the forensic characteristics of any illegal act. Indeed, the specified element is characterized by constant correlation with all other components of the specified scientific category. In the context of criminal proceedings initiated under Art. 296 of the Criminal Code of Ukraine, the method of execution does not lose its importance, but, on the contrary, even increases its importance. Because hooligan actions have various methods of direct execution, as well as methods of preparation and concealment. It is noted that hooligans can implement measures to prepare for their commission, in particular: developing a plan of hooligan actions; selection of the object of encroachment; searching for, adapting and preparing tools and means of illegal actions; selection of accomplices and distribution of roles between them. The following ways of directly committing hooliganism were found out, such as: cynical body movements in combination with obscene swearing; disturbing the peace of citizens in public places; resistance to representatives of law enforcement agencies; causing bodily harm to law enforcement officers; use of firearms, cold weapons, specially adapted objects for inflicting bodily injuries; violation of the normal operation of enterprises, institutions, organizations; use of pyrotechnics. The following methods of concealing hooligan actions have been established, such as: disappearing from the place of a violent act; disappearing from the scene of the crime using a motor vehicle; destruction of tools of illegal activity; liquidation of clothes, shoes; giving false testimony, including an alibi; refusal to testify.